Financial technologies and the effectiveness of monetary policy transmission - Hasan, Iftekhar,Kwak, Boreum,Li, Xiang (Halle Institute for Economic Research (IWH) - Member of the Leibniz Association, 2023)
This study investigates whether and how financial technologies (FinTech) influence the effectiveness of monetary policy transmission. We use an interacted panel vector autoregression model to explore how the effects of monetary policy shocks change with regional-level FinTech adoption. Results indicate that FinTech adoption generally mitigates monetary policy transmission to real GDP, consumer prices, bank loans, and housing prices, with the weakened transmission to bank loan growth being the most pronounced. The relaxed financial constraint, regulatory arbitrage, and intensified competition are the possible mechanisms underlying the mitigated transmission.
urn:nbn:de:gbv:3:2-953124
Keywords: Graue Literatur; monetary policy; financial technology; interacted panel VAR